2020
DOI: 10.1371/journal.pone.0244349
|View full text |Cite
|
Sign up to set email alerts
|

Positive association of angiotensin II receptor blockers, not angiotensin-converting enzyme inhibitors, with an increased vulnerability to SARS-CoV-2 infection in patients hospitalized for suspected COVID-19 pneumonia

Abstract: Background Angiotensin-converting enzyme 2 is the receptor that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) uses for entry into lung cells. Because ACE-2 may be modulated by angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs), there is concern that patients treated with ACEIs and ARBs are at higher risk of coronavirus disease 2019 (COVID-19) pneumonia. Aim This study sought to analyze the association of COVID-19 pneumonia with previous treatment with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…After removing irrelevant items based on the title and abstract, 141 studies were deemed for full-text reading. A total of 49 numbers of articles were used in quantitative analysis [ 12 , 21 – 69 ]. The reason for article inclusion and exclusion is shown in the PRISMA flow (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing irrelevant items based on the title and abstract, 141 studies were deemed for full-text reading. A total of 49 numbers of articles were used in quantitative analysis [ 12 , 21 – 69 ]. The reason for article inclusion and exclusion is shown in the PRISMA flow (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 49 studies with 83,269 of COVID-19 patients (RAASi n = 34,691; non-RAASi n = 48,578) were included in the study [ 12 , 21 – 69 ]. The included study population had confirmed COVID-19 diagnosis by nasopharyngeal reverse transcriptase-polymerase chain reaction (RT-PCR).…”
Section: Resultsmentioning
confidence: 99%